2020
DOI: 10.1159/000511627
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Functional Outcome in Patients with Acute Stroke by Measuring tRNA Derivatives

Abstract: <b><i>Background and Purpose:</i></b> Transfer RNA (tRNA) is a noncoding RNA that delivers amino acids to ribosomes for protein synthesis. tRNA is also involved in cell stress response programs. Oxidative stress induces direct conformational change in tRNA structure that promotes subsequent tRNA fragmentation. Using an antibody against tRNA-specific modified nucleoside 1-methyladenosine (m1A), we can detect tRNA derivatives such as conformationally changed tRNA, tRNA-derived fragments, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 22 publications
1
5
0
Order By: Relevance
“…A previous study compared ischemic and hemorrhagic stroke patients with healthy control subjects and revealed that a significant elevation of N1-methyladenosine was observed in the plasma of stroke patients. This elevation was correlated with the infarction size and the hemorrhage volume, suggesting the potential of N1-methyladenosine as a biomarker for stroke [70,71]. Herein, N1-methyladenosine demonstrated a role as a risk factor among different ischemic stroke subtypes, confirming the previously mentioned conclusion.…”
Section: Elevated Cholesterol Levels Induce Atherosclerosissupporting
confidence: 87%
“…A previous study compared ischemic and hemorrhagic stroke patients with healthy control subjects and revealed that a significant elevation of N1-methyladenosine was observed in the plasma of stroke patients. This elevation was correlated with the infarction size and the hemorrhage volume, suggesting the potential of N1-methyladenosine as a biomarker for stroke [70,71]. Herein, N1-methyladenosine demonstrated a role as a risk factor among different ischemic stroke subtypes, confirming the previously mentioned conclusion.…”
Section: Elevated Cholesterol Levels Induce Atherosclerosissupporting
confidence: 87%
“…Our group, as well as others, have shown that tRFs have potential as circulating biomarkers in, for example, acute stroke. [35][36][37] It has also been demonstrated that tRFs can perform all sorts of regulatory functions, including regulation of protein translation, microRNA-like functions by base-pairing with mRNAs, and interaction with RNA-binding proteins. 38,39 Furthermore, tRFs have been shown to be functionally active in modulating cardiac and skeletal muscle function and endothelial function but also in inhibition of angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…The presence and levels of these tRFs are significantly correlated with the degree of cerebral damage, relating to the size of the infarct in ischemic strokes and the volume of the hematoma in hemorrhagic strokes. These observations suggest that stress-induced tRFs could serve as biomarkers for evaluating cerebral damage and might predict the functional outcomes in stroke patients [238]. tRFs are implicated in important biological processes that are integral to the pathogenesis of stroke, including apoptosis, oxidative stress response, microglial activation, and angiogenesis.…”
Section: The Role Of Trna Dysregulation In Strokementioning
confidence: 91%